Faktor-Faktor yang Mempengaruhi Kecenderungan Penerimaan Opini Audit Going Concern pada Perusahaan Manufaktur (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2010-2014) - Sajiwo, Sakaesa Raganiyan (2016)
The Company was established with the aim to maintain the viability (going concern). Business continuity in a company affected by the auditor's opinion. This study aims to determine the effect of audit quality, the company's financial condition, the audit opinion of the previous year, the company's growth, company size, and debt (debt to equity ratio) against the going-concern audit opinion. The study included 8 companies listed in the Indonesia Stock Exchange (IDX) with a period of 5 years of research carried out during the year 2010 to 2014. This study uses secondary data derived from the Indonesian Capital Market Directory (ICMD) and the Indonesia Stock Exchange (BEI). Population in the study of all manufacturing companies listed in Indonesia Stock Exchange. The research sample was determined by purposive sampling method. Testing the hypothesis in this study using logistic regression analysis. Based on the results of this research is that the quality of the audit, the financial condition of the company, the company's growth, company size, and debt (debt to equity ratio) does not affect the going concern audit opinion. The results support the research of Samita (2015), Setyarno et al. (2006), Widyantari (2011), Januarti and Fitrianasari (2008). While the previous year's audit opinion affect the going concern audit opinion. The results support the research of Ramadhany (2004), Fanny and Saputra (2000). Keywords: quality audit, the financial condition of the company, the audit opinion of the previous year, the company's growth, company size, and debt (debt to equity ratio), going concern audit opinion